Increased cerebrospinal fluid levels of cytokines monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1β (MIP-1β) in patients with amyotrophic lateral sclerosis - H.R. Martínez (Neurología (English Edition), 2020)
Introduction: Neuroinflammation has recently been described in amyotrophic lateral sclerosis (ALS). However, the precise role of such proinflammatory cytokines as monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-1β (MIP-1β) in ALS has not yet been determined. In this study, we determined cerebrospinal fluid (CSF) MCP-1 and MIP-1β levels and assessed their association with the duration and severity of ALS. Methods: Concentrations of MCP-1 and MIP-1β were determined in the CSF of 77 patients diagnosed with ALS and 13 controls. Cytokine levels were analysed in relation to ALS duration (< 12 months vs > 12 months) and severity (< 30 points vs > 30 points on the ALS Functional Rating Scale administered at hospital admission). Results: Higher CSF MIP-1β (10.68 pg/mL vs 4.69 pg/mL, P < .0001) and MCP-1 (234.89 pg/mL vs 160.95 pg/mL, P = .011) levels were found in the 77 patients with ALS compared to controls. There were no differences in levels of either cytokine in relation to disease duration or severity. However, we did observe a significant positive correlation between MIP-1β and MCP-1 in patients with ALS. Conclusions: The increase in MIP-1β and MCP-1 levels suggests that these cytokines may have a synergistic effect on ALS pathogenesis. However, in our cohort, no association was found with either the duration or the clinical severity of the disease. Resumen: Introducción: En la esclerosis lateral amiotrófica (ELA) se ha descrito recientemente la presencia de neuroinflamación. Sin embargo, no se ha definido el rol de citoquinas proinflamatrorias como la proteína quimiotáctica de monocitos-1 (MCP-1) y la proteína inflamatoria macrofágica-1β (MIP-1β) en ELA. En este estudio evaluamos niveles de MCP-1 y MIP-1β en líquido cefalorraquídeo (LCR), analizando su participación en la duración y gravedad de la ELA. Métodos: En 77 pacientes con ELA definida y 13 sujetos controles, se comparó el nivel de citoquinas MCP-1 y MIP-1β en LCR. Se analizaron estos niveles con relación a la duración de la ELA (< 12 meses vs. > 12 meses) y a la gravedad de esta determinada mediante el puntaje obtenido al ingreso en la escala funcional estratificada de la ELA (< 30 puntos vs. > 30 puntos). Resultados: En los 77 pacientes con ELA, se encontraron aumentados los niveles de MIP-1β (4,69 pg/ml vs. 10,68 pg/ml, p < 0,0001) y MCP-1 (160,95 pg/ml vs. 234,89 pg/ml, p = 0,011) en comparación con sujetos controles. No se observó diferencia de los niveles de estas citoquinas con la duración o la gravedad de la enfermedad. Sin embargo, observamos una correlación positiva significativa entre MIP-1β y MCP-1 en pacientes con ELA. Conclusiones: El aumento de MIP-1β y MCP-1 sugiere que estas citoquinas parecen tener un efecto sinérgico en la patogénesis de la ELA. Sin embargo, en nuestra cohorte no se asociaron con la duración o la gravedad de la ELA.